2005
DOI: 10.1590/s0034-71672005000500007
|View full text |Cite
|
Sign up to set email alerts
|

Perfil do adolescente que tenta suicídio em uma unidade de emergência

Abstract: Emergency Units frequently assist suicide attempts. It is important to study this phenomenon in adolescence, since this is a conflict period. This study aimed to outline an epidemiological profile of adolescents admitted in an Emergency Unit, who were diagnosed as suicide attempters. Thus, we examined the records of adolescents admitted at this Unit as suicide attempters in 2002. The results revealed that 77.8% of the cases are characterized as follows: female, predominant age range between 15 and 19 years old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
19

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 3 publications
3
11
0
19
Order By: Relevance
“…poisoning, seeking a "slower and sweeter" form of death (25,26) . The results of the present study corroborate the statements of a number of authors regarding self-intoxication as the method generally used by female adolescents during a suicide attempt, involving the ingestion of medication or poisons and allowing a greater possibility of being saved (1,7,17,27,28) . Household pesticides were the most commonly used poisons, followed by medications.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…poisoning, seeking a "slower and sweeter" form of death (25,26) . The results of the present study corroborate the statements of a number of authors regarding self-intoxication as the method generally used by female adolescents during a suicide attempt, involving the ingestion of medication or poisons and allowing a greater possibility of being saved (1,7,17,27,28) . Household pesticides were the most commonly used poisons, followed by medications.…”
Section: Resultssupporting
confidence: 89%
“…This finding is alarming, as this problem is further aggravated by the encouragement of selfmedication in the media, the lack of primary pharmaceutical care, the indiscriminate medical prescription of psychoactive drugs and inadequate storage in the home (29,16) . Previous studies report that pharmaceutical substances have been the most frequent category of intentional intoxication in adolescence, especially among the female gender (7,24,30) . However, this present study found that pesticides were the method of choice for the majority of female adolescents, although other studies have reported that the ingestion of these chemical substances and other more violent methods are more employed by the male gender (1,16,30) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations